Mycobacterium avium subsp. paratuberculosis (MAP) molecular diversity in cattle, sheep, and goats from Latin America and the Caribbean: a systematic review (2021)
ABSTRACT: This study aimed to systematically collect and appraise the scientifc evidence to answer the research question: What MAP genotypes have been isolated from cattle, sheep, and goats in Latin America and the Caribbean? An electronic search was conducted on three platforms (i.e., OVID®, Web of Science®, SciELO) as well as on the proceedings of the International Colloquium on Paratuberculosis. Inclusion and exclusion criteria were defned a priori and conserved through the systematic process and only articles published in peer-reviewed journals were considered. A total of 26 articles met the defnitive inclusion criteria. All were published in English, in 15 diferent journals, and between 1989 and 2020. The relevant articles reported the use of six diferent genotyping techniques (i.e., polymerase chain reaction-restriction endonuclease analysis, restriction fragment length polymorphism, type-specifc-PCR, mycobacterial interspersed repetitive units-variable number of tandem repeats, multi-locus short sequence repeat, single nucleotide polymorphism) in isolates from seven countries. Genotypes found so far in the region using typing techniques were mainly C type. MIRU-VNTR mostly reported INMV 1, INMV 2, and INMV 11 subtypes, among others. MLSSR reported genotypes from four diferent countries, reporting nine diferent subtypes of which 7g–10g–4ggt was the most common for loci 1, 2, and 8, respectively. Regardless the high diversity of techniques used so far to genotype Latin American and Caribbean MAP isolates, the original question of this systematic review has been answered. In addition, a relative genetic similarity between MAP strains recovered from cattle, goats, and sheep unrelatedly of the matrix and geographic origin was identifed.